2010
DOI: 10.1111/j.1532-5415.2010.03168.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial on Preventing Pressure Ulcers with Wheelchair Seat Cushions

Abstract: Objectives To determine the efficacy of skin protection wheelchair seat cushions in preventing pressure ulcers in the elderly, nursing home population Design Clinical trial with participants assigned at random to either a skin protection or segmented foam cushion. Two hundred thirty two participants were recruited between June 2004 and May 2008 and followed for 6 months or until pressure ulcer incidence. Setting Twelve nursing homes Participants Nursing home residents’ age ≥ 65, using wheelchairs ≥6 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 17 publications
1
57
1
3
Order By: Relevance
“…Employing more therapists with seating expertise increases institutional costs; however, the potential reduction in inappropriate wheelchair prescription is likely to counterbalance this additional expenditure. For example, a recent randomized controlled trial demonstrated a significant reduction in sitting-acquired pressure ulcers in nursing home residents when a properly fitted wheelchair and cushion were provided by a seating specialist [24] . The 22% prevalence rate in two Vancouver nursing homes reported by Bourbonniere et al [14] is well below those observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Employing more therapists with seating expertise increases institutional costs; however, the potential reduction in inappropriate wheelchair prescription is likely to counterbalance this additional expenditure. For example, a recent randomized controlled trial demonstrated a significant reduction in sitting-acquired pressure ulcers in nursing home residents when a properly fitted wheelchair and cushion were provided by a seating specialist [24] . The 22% prevalence rate in two Vancouver nursing homes reported by Bourbonniere et al [14] is well below those observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Returning to the wheelchair cushion example: the occupationbased therapist not only considers a wheelchair cushion for its effectiveness in preventing the formation of decubitus ulcers but also for its ability to support clients comfortably and safely while allowing them to engage in their occupations. Presently, the majority of the literature on wheelchair cushions provides evidence regarding pressure-sore prevention or wound care (e.g., Brienza et al, 2010). This is insufficient; to advance occupation-based practice, research on wheelchair cushions must examine outcomes not only in relation to decubitus ulcers but also to occupational engagement, in safety and with comfort.…”
mentioning
confidence: 99%
“…Este resultado se aproximou de duas pesquisas com pacientes acamados no domicílio que demonstraram este perfil etário, com médias de idade de 86,7 anos (± 7,6) (BRIENZA et al, 2010), e 77,6 (± 11,3) (MORAES et al, 2012). Segundo Chayamiti e Caliri (2010) a idade avançada é apontada como um dos mais relevantes fatores envolvidos na fisiopatogênese da UPP.…”
Section: Discussõesunclassified
“…Brienza et al (2010) têm referido que a resistência em pacientes com baixa mobilidade e imersão inadequada nas superfícies almofadas e colchões pode conduzir a uma pressão de indução de isquemia prolongada e de cisalhamento que se acredita ser o fator primário que conduz ao desenvolvimento de UPP.…”
Section: Discussõesunclassified
See 1 more Smart Citation